The Role of Postoperative Antibiotics in Mandible Fractures: A Systematic Review of the Literature. Issue 3 (September 2015) - Shridharani, Sachin M.; Berli, Jens; Manson, Paul N.; Tufaro, Anthony P.; Rodriguez, Eduardo D.
Abstract : Introduction: Little debate exists regarding the use of preoperative and perioperative antibiotic prophylaxis in the setting of mandibular fracture management; however, employing postoperative prophylactic antibiotics remains an inexact science based on experience rather than evidence. In this systematic review, the authors evaluate scientific literature and report results of an international survey that provide information regarding current practices of the plastic surgery community. Methods: Systematic literature review was performed using Medline, Embase, PubMed, and Cochrane databases to identify studies evaluating use of antibiotics in patients suffering from mandible fractures. Level 1, 2, and large retrospective studies were included. Case reports were excluded. Additionally, an E-survey was distributed to all ASPS members and data were collected over a 5-month period through SurveyMonkey. Results: Four hundred twenty-seven articles published before December 2012 were identified. Seventy-one articles met inclusion criteria. Five articles remained when exclusion criteria were applied. ASPS member survey demonstrated 13% response rate (687 responses/5299 questionnaires). Of respondents, 75% placed patients (ORIF group) with open mandible fractures on prophylactic antibiotics for up to 3 days (44.1%), 1 week (54.8%), and more than 1 week (1.1%). Of respondents, 51% placed patients (ORIF group) with closed mandible fracture on prophylactic antibiotics for up to 3 days (50.5%), 1 week (48.6%), and more than 1 week (1%). Conclusion: Critical literature review demonstrates a trend towards no postoperative antibiotic coverage (>24 hours) in patients undergoing mandibular ORIF. There is further need for prospective, randomized control trials with a standardized regimen. Our survey elucidates the variability of plastic surgeons' clinical practices.